Neighborhood Social Capital and Achieved Mobility of Older Adults. (December 2014) - Rosso, Andrea L.; Tabb, Loni P.; Grubesic, Tony H.; Taylor, Jennifer A.; Michael, Yvonne L.
Objective: Evaluate associations of neighborhood social capital and mobility of older adults.Method: A community-based survey (Philadelphia, 2010) assessed mobility (Life-Space Assessment [LSA]; range = 0-104) of older adults ( n = 675, census tracts = 256). Social capital was assessed for all adults interviewed from 2002-2010 ( n = 13, 822, census tracts = 374). Generalized estimating equations adjusted for individual- and neighborhood-level characteristics estimated mean differences and 95% confidence intervals (CIs) in mobility by social capital tertiles. Interactions by self-rated health, living arrangement, and race were tested.Results: Social capital was not associated with mobility after adjustment for other neighborhood characteristics (mean difference for highest versus lowest tertile social capital = 0.79, 95% CI = [−3.3, 4.8]). We observed no significant interactions. In models stratified by race, Black participants had higher mobility in high social capital neighborhoods (mean difference = 7.4, CI = [1.0, 13.7]).Discussion: Social capital may not contribute as much as other neighborhood characteristics to mobility. Interactions between neighborhood and individual-level characteristics should be considered in research on mobility.